Tik Tok in Improving Students' Speaking Skills in the English for Business Course - Rizky Mirani Desi Pratama; Dwi Puji Hastuti (Wanastra: Jurnal Bahasa dan Sastra, 2023)
Learning media in the digital era must be aligned with technological developments. The learning media chosen must be interesting and attached to students. The Tik Tok application is currently popular with many people, including the students of administrasi bisnis department, Universitas Bina Sarana Informatika. Departing from these reasons, the researchers took the initiative to implement the Tik Tok application as a medium interesting and fun learning in delivering material in English for Business courses. This study aims to find out how effective the Tik Tok application is in improving the speaking skills of students majoring in business administration at the Universitas Bina Sarana Informatika. Qualitative method is used for analyzing the recorded video on Tik Tok application that were produced by the students as well as processing of questionnaires on student views regarding the use of tick tock media in learning in English for Business courses. The result indicated that the use of the Tik Tok application is considered quite effective in developing students' speaking skills. This can be seen from the results of the recordings sent to lecturers, students are more relaxed and not tense when speaking English using Tik Tok. This was also corroborated by the results of filling out the questionnaire which stated that the Tik Tok application was an innovation in learning English, which made students more relaxed and enjoyed the teaching and learning process and eliminated the mindset that learning English is difficult.